KINERJA WANITA NELAYAN DALAM SEKTOR INDUSTRI RUMAH TANGGA PASCA KRISIS 1997 (STUDI SOSIAL MASYARAKAT NELAYAN KOTA SEMARANG) - Muji Utami, Santi (Forum Ilmu Sosial, 2011)
In addressing the issue of employment opportunities for women, the empowerment of economic institutions rooted in the community such as domestic industry is an alternative that is very precise because its activities is around the home (home - base - production), in their own homes and independent business. This writing is trying to describe about a woman’s basic fshing skills, the type of home industry, her contribution to the economy of a family of fshermen, and fshermen woman constraint factor in gaining employment in the domestic industrial sector.The method used in this research is a qualitative method using triangulation techniques. Analysis of data uses a model of interactive analysis The study subjects were women who live in the fshing village, in the productive age status as wife or widow who became head of the family.Based on the results and the discussion, it can be concluded that the skills / basic skills possessed by most of the fshermen are based on the experience of women which is passed by his predecessors. Type or range of jobs that can be entered by the wives of fshermen in the household sector is in the form of salting, curing and manufacture pindang. Other kinds of jobs that run at large is still associated with fshing activities. The contribution of fshermen working women, will add to the household fnances because the income of husband is insuffcient to fulfll the needs of everyday life. Women fshermen involved in the activity of earning life is active agents of socio-economic changes of fshing communities. Factors inhibiting women’s work in domestic industrial sector is the low motivation to develop the business, a relatively low education levels, limited capital, ability and skills possessed Keywords : fshermen women, industry